RELATIONSHIP OF WASTE MANAGEMENT WITH KNOWLEDGE, ATTITUDE AND PARTICIPATION OF TRADERS IN THE TRADITIONAL TERONG MARKET IN MAKASSAR (International Conference on Social and Islamic Studies, 2021)
Terong Traditional Market is one of the traditional markets located in the center of Makassar City. This traditional market is every day a busy market visited by the community, because this market sells various types of merchandise, so this traditional market produces waste every day. This study aims to determine by describing and analyzing the relationship between knowledge, attitudes and availability of facilities with the participation of traders in waste management at the Terong Traditional Market in Makassar City. This research is a is quantitative descriptive research to describe, explain, or summarize various conditions, situations, phenomena, or various research variables. The test results from the study are described by tables and the percentage values obtained by the Terong Traditional Market in Makassar City. From the results of the research that has been done, it can be concluded that there is a significant relationship between knowledge, attitudes and availability of facilities with the participation of traders in waste management at the Terong Traditional Market.